2010
DOI: 10.3835/plantgenome2010.04.0010
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐size Variation in Switchgrass ( Panicum virgatum ): Flow Cytometry and Cytology Reveal Rampant Aneuploidy

Abstract: Switchgrass (Panicum virgatum L.), a native perennial dominant of the prairies of North America, has been targeted as a model herbaceous species for biofeedstock development. A fl owcytometric survey of a core set of 11 primarily upland polyploid switchgrass accessions indicated that there was considerable variation in genome size within each accession, particularly at the octoploid (2n = 8X = 72 chromosome) ploidy level. Highly variable chromosome counts in mitotic cell preparations indicated that aneuploidy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 84 publications
(144 reference statements)
5
89
0
Order By: Relevance
“…FISH, using pTa71 as a probe, detected two pairs of telomeric hybridization sites (Figure 4). A similar pTa71 FISH pattern was previously observed in all tetraploid accessions of switchgrass analyzed [39]. This indicates that the number and location of nucleolus organizer regions (NORs) in tetraploid accessions is highly conserved.…”
Section: Chromosomal Constitutions Of Regenerated Autooctoploid Plantssupporting
confidence: 59%
See 2 more Smart Citations
“…FISH, using pTa71 as a probe, detected two pairs of telomeric hybridization sites (Figure 4). A similar pTa71 FISH pattern was previously observed in all tetraploid accessions of switchgrass analyzed [39]. This indicates that the number and location of nucleolus organizer regions (NORs) in tetraploid accessions is highly conserved.…”
Section: Chromosomal Constitutions Of Regenerated Autooctoploid Plantssupporting
confidence: 59%
“…However, this pattern is unique and very different from the octoploid accessions of switchgrass that were previously analyzed [39]. Those octoploid accessions were highly variable in NOR size and number and also differed in the chromosomal location of the probe.…”
Section: Chromosomal Constitutions Of Regenerated Autooctoploid Plantsmentioning
confidence: 61%
See 1 more Smart Citation
“…Aneuploidy has been observed in tetraploid as well as octoploid switchgrass, but the frequency is much higher in the latter [27]. The same authors also demonstrated through in situ hybridization of a ribosomal probe to mitotic metaphase chromosomes that many octoploids showed chromosomal rearrangements.…”
Section: Linkage Mapsmentioning
confidence: 60%
“…The same authors also demonstrated through in situ hybridization of a ribosomal probe to mitotic metaphase chromosomes that many octoploids showed chromosomal rearrangements. No such rearrangements were observed in the tetraploids examined, but the resolution of this study was low since only a single probe was used [27].…”
Section: Linkage Mapsmentioning
confidence: 98%